Mice Expressing Low Levels of CalDAG-GEFI Exhibit Markedly Impaired Platelet Activation With Minor Impact on Hemostasis. Issue 9 (September 2016) - Piatt, Raymond; Paul, David S.; Lee, Robert H.; McKenzie, Steven E.; Parise, Leslie V.; Cowley, Dale O.; Cooley, Brian C.; Bergmeier, Wolfgang
Abstract : Objective—: The tight regulation of platelet adhesiveness, mediated by the αIIbβ3 integrin, is critical for hemostasis and prevention of thrombosis. We recently demonstrated that integrin affinity in platelets is controlled by the guanine nucleotide exchange factor, CalDAG-GEFI (CD-GEFI), and its target, RAP1. In this study, we investigated whether low-level expression of CD-GEFI leads to protection from thrombosis without pathological bleeding in mice. Approach and Results—: Cdg1 low mice were generated by knockin of human CD-GEFI cDNA into the mouse Cdg1 locus. CD-GEFI expression in platelets from Cdg1 low mice was reduced by ≈90% when compared with controls. Activation of RAP1 and αIIbβ3 was abolished at low agonist concentrations and partially inhibited at high agonist concentrations in Cdg1 low platelets. Consistently, the aggregation response of Cdg1 low platelets was weaker than that of wild-type platelets, but more efficient than that observed in Cdg1 −/− platelets. Importantly, Cdg1 low mice were strongly protected from arterial and immune complex–mediated thrombosis, with only minimal impact on primary hemostasis. Conclusions—: Together, our studies suggest the partial inhibition of CD-GEFI function as a powerful new approach to safely prevent thrombotic complications. Abstract : Supplemental Digital Content is available in the text.